Medical versus Surgical Treatment of a Primary Tuberculous Pleural Peel - Richard Long; Anne Fanning; Ciaran McNamee; James Barrie; Lakshmi Puttagunta (Canadian Respiratory Journal)
The role and timing of surgical decortication in the management of a primary tuberculous pleural peel remains controversial. The present report describes the case of a young man with an extensive primary tuberculous pleural peel that responded dramatically to medical therapy. A serious attempt at surgical decortication three weeks into antituberculous drug therapy may have removed some compressive aspects of the peel, facilitating lung expansion. However, it had almost no measurable impact on the size of peel and was technically very difficult. Response to treatment was measured anatomically (computed tomography scans) and physiologically (pulmonary function tests).